Game with Central Symmetry on a Rectangular Board - Toni Chehlarova; Mladen Valkov (Педагогически форум)
A game with central symmetry on a rectangular board, created with Unity3D, is presented. It is available for both PC and Android with mixed reality. The purpose of creating the game is to provide conditions for the development of digital and mathematical competence in students through play in both formal and non-formal learning. Four options are described, depending on the presence or absence of animation, as well as the limitation of working time.